The RTE Act Amendments How Progressive are they? - Ahuja, Anupam (JOURNAL OF INDIAN EDUCATION, 2014)
The enactment of the RTE Act 2009 marked a historic moment for the children of our country. A landmark legislation, it makes elementary education a fundamental right for all children between the ages of 6-14 years. It has brought to centre stage the importance of formal schooling for all children, including children with disabilities and focuses on bringing about the much needed systemic changes. The recent amendments strengthen the commitment of education for all children with disabilities in our country and if applied in true spirit, will result in real and important gains for their education in the mainstream school system. There needs to be a strong focus on the preparation of this system, so that children with disabilities can get the required support to access and participate in the system as equal partners. Monitoring will be required in the coming years on how education and rehabilitation grow and complement each other. This article highlights the amendment regarding home-based education for children with severe and multiple disabilities and the mixed response it has received. It urges the reader to reflect on how progressive is this move?